THE RELATIONSHIP BETWEEN DISCIPLINE AND THE PERFORMANCE OF EMPLOYEES OF PDAM TIRTA INDRA RENGAT INDRAGIRI HULU DISTRICT (JURNAL ECONOMICA : Research of Economic And Economic Education, 2019)
The aim of this research to determine the relationship of discipline with the performance of employees of PDAM Tirta Indra Rengat, Indragiri Hulu Regency. This Research is a quantitative. Primary data were obtained through a questionnaire distributed to 53 employees. Data analysis techniques used in the research is conducted are Product Moment Correlation and t-Test through the SPSS application. The results of the study are the existence of a disciplinary relationship with significant performance and are positive and is in the medium category.Keyword: Discipline, Performance